1983
DOI: 10.1007/bf01571117
|View full text |Cite
|
Sign up to set email alerts
|

Reduction malar plasty

Abstract: Among Caucasians, augmentation malar plasty is occasionally performed, but, most often Orientals complain of the prominent zygoma and want an oval face. The procedure of the reduction malar plasty is not reported here. Instead, this article discusses the authors' method of reduction malar plasty and presents several cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(24 citation statements)
references
References 2 publications
0
24
0
Order By: Relevance
“…The aim of this procedure is to obtain softer and rounder facial contours. Since Onizuka et al 1 reported bone shaving via an intraoral incision, many other methods have been introduced.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The aim of this procedure is to obtain softer and rounder facial contours. Since Onizuka et al 1 reported bone shaving via an intraoral incision, many other methods have been introduced.…”
Section: Discussionmentioning
confidence: 99%
“…Since Onizuka et al 1 first described a surgical technique based on chiseling and shaving via an intraoral incision, a number of different surgical techniques have been developed for reducing malar bone volume. [1][2][3][4][5][6][7][8][9][10] Current surgical methods can be divided based on the following aspects: (1) type of approach: coronal incision, 3 intraoral incision, 4,6,7,[9][10][11] or a combination of intraoral and preauricular incisions 5,8 ; and (2) type of ostectomy: parallel, 5 large L-shaped, 6,8 or small L-shaped. 11,12 Other aspects include shaving or grinding, 7 involvement of a greenstick fracture, 4 and type of bone fixation.…”
mentioning
confidence: 99%
“…The reduction shaving of the zygomatic bone was first introduced by Onizuka et al 2 From then on, many kinds of surgical procedures have been developed. 3Y10 According to the site of osteotomy, the existing operation can be classified into anterior osteotomy and anterior plus posterior osteotomy on the zygomatic arch.…”
Section: Discussionmentioning
confidence: 99%
“…The design of the osteotomy is as follows (Figure 5A): (1) The starting point of the osteotomy is the intersection point where the occlusal plane meets the posterior edge of the ramus (point A). (2) The end point of the osteotomy is the intersection point where the vertical line from the second premolar meets the edge of the mandible (point B).…”
Section: Inclined-fullness Osteotomy In the Mandibular Angle And Marginmentioning
confidence: 99%